Design and Research of CAS‐CIG for Earth System Models. Issue 7 (8th July 2020) - Wang, T.; Jiang, J.; Zhang, M.; Zhang, H.; He, J.; Hao, H.; Chi, X.
Abstract: The Chinese Academy of Sciences Coupling Interface Generator (CAS‐CIG) is designed to address the complexities of the development and coupling of different component models in Earth System Models based on the Coupler 7 of the Community Earth System Model (CESM). Its application in the Chinese Academy of Sciences Earth System Model (CAS‐ESM) is described. The CAS‐CIG automatically generates the coupler code through a simple configuration file when a component model is accessed, enabling different component models to be easily ported to CPL7 to create simulation cases. Combined with the automatic generation of compile scripts, the precompilation and run directories are directly formed. The component model integration, model selection, experimental setup, and platform migration can be all accomplished in the CAS‐CIG. Verification of the CAS‐CIG is presented to show that the automatically generated codes can identically reproduce the simulation results of CAS‐ESM. CAS‐CIG presents a software tool for modeling centers to investigate the impact of component model selections on simulations of climate and weather. Key Points: A coupling interface generator for Earth System Models is designed and implemented The technology of coupling interface generation is researched The experimental results prove the correctness of the coupling interface generator